Thermally sensitive micelles self-assembled from poly(N- isopropylacrylamide-co-N,N-dimethylacrylamide)-b-poly(d,l-lactide-co-glycolide) for controlled delivery of paclitaxel - Liu, S.Q. (2014)
Molecular BioSystems